Formative evaluation impacting the results of summative evaluation-a feedback based cross sectional study carried out among instructors of an international medical school - Alsalhanie, Kusai M.; Das, Sanjib; Abdus-Samad, Sulaimaan (International Journal of Research in Medical Sciences, 2017)
Background: In all forms of teaching worldwide, evaluation is fundamental in measurement of the students’ acquisition and understanding of the material covered. Evaluation is divided into two separate forms. The goal of formative evaluation is to monitor students learning and provide ongoing students feedback. This in turn improves teaching and help finding strengths and weaknesses of students. Summative evaluation on the other hand is to evaluate students learning at the end of the instructional unit to compare students’ performance with some other standards. Currently several types of formative evaluation activities are in practice at our institution. This study was performed to explore the views of faculties as to the impact of formative evaluation on summative evaluation within the MD program. Methods: A cross sectional descriptive study was conducted using a questionnaire to record the opinions and then the data was collected, analysed and interpreted. Results: All respondents opined that formative evaluation aids the students in isolating specific weak areas. All faculties indicated that, formative evaluation is important for them as it aids in targeting problem areas within their classes. A sizable percentage of respondents also supported that formative evaluation helped instilling the need for regular study and intensive learning within their students. Furthermore, many respondents (75%) didn’t accept the statement that frequent formative evaluation impeded their students’ focussed learning leading to deficient performance in summative evaluation. Conclusions: Formative evaluation positively impacts summative ones in many ways.